Dynamic model of a novel thermogravity rotary actuator for solar energy harvesting. (30th March 2020) - Muhammad, Wasif; Irshad, Muhammad Jehanzeb; Miran, Sajjad; Haider, Muhammad Salman
Summary: The direct conversion of thermal energy to mechanical energy is always been a challenging but demanding problem. In this article, we presented a nonconventional direct conversion mechanism of the readily available solar thermal and gravity energy to rotational mechanical energy. The developed rotating assembly affixed concentrically with a plurality of actuating arms harnesses the integrated solar‐gravity energy. Each actuating arm shifts the center of gravity of the attached solid mass with concentrated solar heating. The alternate shift in the center of gravity of each actuating arm with exposure to solar radiation produces a continuous revolution of rotating assembly around its axis of rotation. With a particular set of the system parameters with Al / Si 3 N 4 bimetallic strip the thermal efficiency of the proposed thermogravity bimetallic strip heat actuator/engine is 12.41% which is 100 times more efficient compared to a gravity‐less thermal engine with same set up. The proposed thermogravity system can generate mechanical power ranges from less than 1 W to 40 kW with a particular set of system parameters. This solar‐gravity rotary actuator is a novel work in this domain which has a huge impact and contribution in the available rotary actuator or energy harvester knowledge.